Intrafetal laser ablation for embryo reduction from dichorionic triplets to dichorionic twins. (5th October 2017) - Chaveeva, P.; Peeva, G.; Pugliese, S. G.; Shterev, A.; Nicolaides, K. H.
ABSTRACT: Objective: To report the outcome of dichorionic (DC) triplet pregnancies reduced to DC twins by laser ablation of the pelvic vessels of one of the monochorionic (MC) twins. Methods: Intrafetal laser embryo reduction (ER) from DC triplets to DC twins was carried out in 61 pregnancies at 11 + 0 to 14 + 3 weeks' gestation. Pregnancy outcome was examined. Results: Intrafetal laser was successfully carried out in all cases, but ultrasound examination within 2 weeks of the procedure demonstrated that the MC cotwin had died in 28 (45.9%) cases and was alive in the other 33 (54.1%). In the DC group, there was one miscarriage at 23 weeks, one neonatal death after delivery at 26 weeks and in the other 31 cases there were two live births at a median gestational age of 35.3 (range, 30.4–38.4) weeks. In the 28 cases in which both MC fetuses died, there was one miscarriage at 16 weeks and in the other 27 cases the separate triplet was liveborn at a median gestation of 38.2 (range, 32.2–42.1) weeks. The overall rate of miscarriage was 3.3% (2/61) and that of preterm birth (PTB) at < 33 weeks was 6.8% (4/59). Conclusions: In the management of DC triplet pregnancies, ER to DC twins by intrafetal laser ablation is associated with lower rates of miscarriage or early PTB, compared with expectant management or ER by fetal intracardiac injection of potassium chloride. However, about half of the pregnancies result in the birth of one rather than two babies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.